Symphony No. 2 in C Minor Resurrection - Mahler, Gustav. 1860-1911 (Colección Dover Miniature Scores, 1993)
This profound work which obsessed Mahler for seven years, is presented here in full score with original instrumentation, bar numbered movements and with ample margins at the bottom of each score page for notes and analysis.